Gas Compressor Station Economic Optimization. (1st March 2012) - Kurz, Rainer; Lubomirsky, Matt; Brun, Klaus
Abstract : When considering gas compressor stations for pipeline projects, the economic success of the entire operation depends to a significant extent on the operation of the compressors involved. In this paper, the basic factors contributing to the economics are outlined, with particular emphasis on the interaction between the pipeline and the compressor station. Typical scenarios are described, highlighting the fact that pipeline operation has to take into account variations in load.